Exploring Inhibitory Control Processes in Highly Superior Autobiographical Memory (HSAM): A Single Case Study - Jessica Talbot; Daniele Gatti; Marta Boccalari; Michela Marchetti; Danilo Mitaritonna; Gianmarco Convertino; Mara Stockner; Giuliana Mazzoni (Journal of Cognition)
Individuals who possess a Highly Superior Autobiographical Memory (HSAM) can remember their own lives in exceptional detail, retrieving specific autobiographical events in response to dates (e.g., 15th April 1995). The phenomenon remains extremely rare, and little is known about why these individuals can remember substantially more than the general population, without being continually flooded by past memories. According to the cognitive inhibition dependency hypothesis, inhibitory processes modulate general autobiographical memory by determining which memories will (and will not) enter one’s consciousness. We hypothesised that these control processes are amplified in HSAM, protecting them from being overwhelmed by their abundance of memories. To explore if cognitive inhibition is exceptional in HSAM, a single case with HSAM (DT) and 20 matched controls completed a battery of 6 tasks assessing various aspects of inhibition (e.g., memory, prepotent motor responses). Participants also completed a screening for obsessive compulsive disorder and autism. Results indicate that DT’s inhibitory functioning is comparable to that of the typical population, and thus not exceptional. We conclude that inhibition is unlikely to be the best explanation for extraordinary remembering and add to the growing body of literature that HSAM can occur in the absence of clinical symptomatology. Results are discussed in relation to future directions of HSAM research.